A nature-inspired betalainic probe for live-cell imaging of Plasmodium-infected erythrocytes. - Letícia Christina Pires Gonçalves (Public Library of Science (PLoS), 2013)
A model betalainic dye was semisynthesized from betanin, the magenta pigment of the red beet, and was effective for live-cell imaging of Plasmodium-infected red blood cells. This water-soluble fluorescent probe is photostable, excitable in the visible region and cell membrane-permeable, and its photophysical properties are not notably pH-sensitive. Fluorescence imaging microscopy of erythrocytes infected with Plasmodium falciparum, a causative agent of malaria in humans, showed that only the parasite was stained. Z-stacking analysis suggested that the probe accumulates proximal to the nucleus of the parasite. Indicaxanthin, one of the natural fluorescent betalains found in the petals of certain flowers, did not stain the parasite or the red blood cell.